The new Russian diplomacy - Ivanov, I. S. (Igorʹ Sergeevich), 1945- (Washington, D.C. : Nixon Center : Brookings Institution Press, 2002)
In this frank and engaging book, foreign minister Igor S. Ivanov describes the evolution of Russian foreign policy since the collapse of the Soviet Union. Drawing on Russia's long diplomatic history, Ivanov analyzes the complex process through which a newly democratic Russia has redefined its foreign policy during a volatile transformation over the last decade. The book includes the text of Russia's Foreign Policy Concept, a Putin administration document that guides the day-to-day activities of the government. Designed to provide the world community with a transparent outline of Russia's foreign policy agenda, the Concept attempts to balance Russia's important role in the new world order with internal pressures to focus on domestic stability. The radical transformation of the past decade has required a complete overhaul of the process by which foreign policy is crafted, implemented, and communicated, according to Ivanov. The Concept delineates the role of parliament in making foreign policy decisions, the interrelationship of the legislative and executive branches, and the apportionment of authority among the president, government, and regional authorities. It also stresses the need to renovate Russia's diplomatic service, whose tradition of professionally trained diplomats dates back to Peter the Great. While acknowledging the impulse to recreate foreign policy from scratch during periods of revolutionary change and radical reform, Ivanov stresses the theoretical and practical importance of continuity. Although the modern political system of the Russian Federation has no analogue in Russian history, Ivanov draws compelling connections between the country's contemporary challenges and the rich legacy of Russian and Soviet diplomacy-in the process invoking the political philosophies of historical Russian leaders from ancient Rus' to Alexander Gorchakov. The New Russian Diplomacy was originally published in Russia, where it received very favorable reviews. This volume is a special edition prepared for American readers with a new introduction and an expanded and updated discussion of the U.S.-Russian relationship.
Foreword / Henry A. Kissinger -- To the American reader -- Overview of Russian foreign policy -- Formation of a new international system -- Regional trends in Russian foreign policy -- New horizons.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Russia (Federation) -- Foreign relations; Relations publiques et politique -- Russie; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- World -- Russian & Former Soviet Union; Diplomatic relations; Russia (Federation); Diplomatieke betrekkingen; Buitenlandse politiek; Rusland